Examining the Impact of Triple Bottom Line Approaches on the Economic Performance of Emirati SMEs - Alowais, Abdelaziz Abdalla; Harb , Sally; Jawas , Khulood (Journal of Ecohumanism, 2025)
This paper serves the purpose of finding statistical and empirical evidence of TBL influenced approaches mediated by Sustainable Supply Chain Management, Sustainable Marketing and Sustainability Oriented Innovation on Economic performance. The paper delved back to foundational theories that shape the traditional management functions into developing them into sustainable practices thus studying the sustainable practices as mediators. Followed by developing positively toned hypotheses as suggested by previous studies and finding measurement scales adapted by previous studies to cover accurate items. The survey results were analyzed using the Jamovi and Warpl_PLS systems to ensure that the hypothesis accepted or rejected followed s two-system rigor calculations. The results point out that all the Triple Bottom line influenced methods all have a strong positive relation with Economic performance and accept 9 hypotheses. Sustainable practices such as Sustainable Supply Chain Management, Sustainable Marketing and Sustainability Oriented Innovation all were statistically partial mediators after using the direct effect, indirect effect and total effect calculations which lead to conclusive results in the Emirati context. The study could support the practical implications of sustainable practices as the empirical evidence shows a strong connection to Economic performance. Thus, the practitioners could influence their current practices to a more sustainable approach influenced by the Triple Bottom line theory.